An assessment of endophytic fungi in needles of three pinus spp. cultivated in South Africa - Kriel, Wilma-Marie (University of the Free State, 1999)
Endophytes, in the strict sense, are organisms that cause symptom less infections in plants. As symptomless mutualists, they can act as biocontrol agents of herbivorous insects and plant diseases. They can also be indicative of host vitality and environmental pollution. Some endophytes, however, are latent pathogens with an endophytic phase. Pine needles are colonised by various species of endophytic fungi. It is well-known that the endophytic biota vary with host species, as well as with time. Therefore the aim of this study was to qualitatively and quantitatively compare endophyte populations within the canopies of Pinas patula, P. radiata and P. elliottii, during winter and summer, and within the canopies of two separate P. radiata trees, over different seasons. Endophytic fungi were isolated from pine needles, sampled in different seasons from various positions within the canopy, by plating surface-sterilised needle sections onto cornmeal agar supplemented with antibiotics. In the first study a significant difference (P < 0.05) in endophyte numbers between samples collected during winter and summer was observed. Pinus patula and P. elliottii were more intensively colonised during winter than summer. In P. radiata, however, the number of fungi isolated in summer was significantly higher than in winter, but the fungal species isolated were consistent. Cydsneusms minus and a sterile white yeast-like fungus were most commonly isolated. Cyclsneusms minus is a latent pathogen causing autumn needle cast, and sterile yeast-like fungus is suspected to be a true endophyte. Similar endophytic fungal species were isolated in the second study, performed on two eight-year-old P. radiata trees. Samples were taken during four seasons from an isolated, solitary tree and one growing in an even-aged, plantation nearby. Five needle fascicles of four different age groups were collected from each tree. One needle per fascicle, including the fascicle sheath, was cut into 12 sections and used for the isolations. In general, fewer endophytes were isolated from the solitary tree than the plantation tree. Qualitative and quantitative differences in endophyte populations were observed within needles as well as between needle age groups and seasons. The aim of the third study was to conduct a qualitative assay of enzyme production of 2 t predominant fungal endophytes isolated from the pine needles. The enzymes assayed included cellulase, pectinase, lipase, laccase, phenol oxidase, protease, B-glucosidase, cytochrome oxidase, and peroxidase. Results were consistent with attributes associated with leaf penetration and longterm residence of fungi within pine needles. All fungi screened produced at least two of the enzymes assayed. Different substrate utilisation patterns suggest biochemical partitioning of nutritional resources by endophytes. The ubiquitous presence of lipolytic activity in all isolates tested, suggests the ability to lyse cuticular waxes in order for penetration to occur. The tolerance of most tested fungi to tannic acid (phenol oxydase production) suggests low sensitivity to phenolic compounds (tannins etc.) normally present in pine needle tissue. Management practices in plantations that reduce or increase the environmental stress on individual trees, thereby influencing endophytic populations, could have distinct beneficial or negative effects on the general vitality of trees. The most important effects of certain practices would be the influence they have on latent pathogens such as C minus. Further investigation of foliar endophytic fungi of intensively managed pine plantations is therefore justified with a view to understand the effects management practices have on their ecology.

Endofiete, in die streng sin van die woord, is organismes wat simptoomlose infeksies in plante veroorsaak. As simptoomlose mutualiste, kan hulle dien as biologiese beheeragente van plantsiektes en plantvretende insekte. Hulle kan ook ‘n aanduiding gee van gasheer lewenskragtigheid en omgewingsbesoedeling. Sommige endofiete is egter latente patogene met ‘n endofitiese fase. Dennenaalde word deur verskeie endofitiese swamspesies gekoloniseer. Dit is wel-bekend dat endofitiese biota kan varieër binne gasheerspesie en ook oor tyd. Die doel van hierdie studie was ‘n kwalitatiewe en kwantitatiewe vergelyking te maak van endofietpopulasies binne die blaredak van Pinus patula, P. radiata en P. elliottii, gedurende die winter en somer, en binne die blaredak van twee aparte P. radiata bome, oor verskeie seisoene. Isolasie van endofitiese swamme uit dennenaalde in verskillende seisoene en posisies binne die blaredak, is gedoen deur stukkies oppervlakgesteriliseerde naalde op mieliemeelagar met atibiotika uit te plaat. In die eerste studie is ‘n betekenisvolle verskil (P<0.05) in endofietgetalle waargeneem tussen monsters wat onderskeidelik in die winter en somer versamel is. Pinus patula en P. elliottii was meer intensief gekoloniseer in die winter as in die somer. In P. radiata, egter, was die hoeveelheid swamme in die somer geïsoleer, betekenisvol meer as in die winter, maar die swamspesie samestelling het konstant gebly. Cyclsneusms minus en ‘n steriele wit gisagtige swam is meer gereeld geïsoleer. Cycisneusms minus is in latente patogeen wat herfs-naaldval veroorsaak, en die steriele gisagtige swam is vermoedelik in egte endofiet. Soortgelyke endofitiese spesies is in die tweede studie geïsoleer. Hierdie studie is op twee agt-jaar-oue P. radiata bome gedoen. Monsters is gedurende vier seisoene versamel van onderskeidelik ‘n alleenstaande boom, en ‘n boom in ‘n nabygeleë plantasie van dieselfde ouderdom. Vyf naaldbondels, van vier verskillende ouderdomsgroepe per tak, op vier takke, is uit elke boom versamel. Een naald per bondel, insluitend die bondelskede, is in 12 stukkies gesny en in die isolasies gebruik. In die algemeen is minder endofiete uit die alleenstaande boom as uit die plantasie-boom geïsoleer. Kwalitatiewe en kwantitatiewe verskille in die endofiet populasies is waargeneem, binne die naalde sowel as binne naald-ouderdomsgroepe en seisoene. Die doel van die derde studie was om ensiem produksie van 21 mees prominente swamendofiete wat uit dennenaalde geïsoleer is kwalitatief te toets. Sellulase, pektinase, lipase, lakkase, fenoloksidase, protease, β-glukosidase, sitochroomoksidase en peroksidase is getoets. Die resultate was in ooreenstemming met eienskappe geassosieër met blaarpenetrasie en langtermyn inwoning van swamme binne dennenaalde. Alle swamme wat getoets is, het ten minste twee ensieme geproduseer. Verskille in substraat afbraakpatrone suggereer biochemiese onderskeiding van voedingsbronne by endofiete. Die alomteenwoordige voorkoms van Iipolitiese aktiwiteit in al die bestudeerde isolate, wil te kenne gee dat hulle oor die vermoë beskik om kutikulêre was af te breek sodat penetrasie kan plaasvind. Die toleransie van meeste (van die getoetsde) swamme teenoor tanniensuur (fenoloksidase produksie), is ‘n aanduiding dat hulle minder sensitief isteenoor fenoliese stowwe (tanniene ens.) wat normaalweg in dennenaaldweefsel teenwoordig is. Bestuurspraktyke in plantasies wat omgewingstremming op individuele bome verminder of vermeerder, en sodoende endofitiese populasies beïnvloed, kan definitiewe voordelige of nadelige effekte op die algemene lewenskragtigheid van bome hê. In hierdie verband sal die invloed van sodanige praktyke op latente patogene C minus van ekonomiese belang wees. Verdere ondersoeke van naaldendofiete in intensief bestuurde plantasies is daarom geregverdig met die vooruitsig om die effekte wat bestuurspraktyke op hul ekologie het, te verstaan.
Dissertation (M.Sc. (Plant Pathology))--University of the Free State,1999
Keywords: Endophyte; Fungi; Gymnospermae; Latent pathogen; Pinus spp; Plant disease; Fungal populations; Endophytic fungi; Plant-fungus relationships